Biosecurity and Vaccines for Emerging Aquatic Animal RNA Viruses - Sohrab Ahmadivand; Ayanna Carla N. Phillips Savage; Dušan Palic (Viruses, 2025)
Emerging RNA viruses pose a critical threat to aquatic animals, leading to significant ecological and economic consequences. Their high mutation rates and genetic adaptability drive rapid evolution, cross-species transmission, and expanding host ranges, complicating disease management. In aquaculture, RNA viruses are responsible for major outbreaks in fish, while DNA viruses predominate in crustaceans. Marine mammals are increasingly affected by morbilliviruses and highly pathogenic avian influenza (HPAI) H5N1, which has caused widespread mortality events in pinniped and cetacean populations, raising concerns about zoonotic spillover. The absence of effective antiviral treatments and the complexity of vaccine development highlight the urgent need for enhanced biosecurity measures. Furthermore, novel vaccine approaches, such as self-assembling protein nanocage platforms, offer promising solutions for RNA virus mitigation. This review provides a comprehensive analysis of the emergence and significance of RNA viruses in aquatic animals over the last two decades, with a particular focus on biosecurity and vaccine development.